Optimal Income Taxation with Unemployment and Wage Responses: A Sufficient Statistics Approach - Kory Kroft; Kavan Kucko; Etienne Lehmann; Johannes Friedrich Schmieder (Center for Economic Studies and ifo Institute (CESifo), 2017)
We derive a sufficient statistics optimal income tax formula in a general model that incorporates unemployment and endogenous wages, to study the shape of the tax and transfer system at the bottom of the income distribution. The sufficient statistics are the macro employment response to taxation and the micro and macro participation responses. We estimate these statistics using policy variation from the U.S. tax and transfer system. Our results suggest that the optimal tax more closely resembles a Negative Income Tax than an Earned Income Tax Credit relative to the case where unemployment and wage responses are not taken into account.
Keywords: 330